VALIDITY AND RELIABILITY OF THE EXPECTED RESULTS OF THE EVALUATION OF CHRONIC WOUND HEALING (RESVECH 2.0) (Estima – Brazilian Journal of Enterostomal Therapy, 2023)
Introduction: Wounds that are difficult to heal are a health problem due to their high prevalence and multifactorial etiologies. Treatment begins with the prescription of the appropriate therapeutic agent, followed by the use of instruments that allow the professional to document wound assessments. Objective: The study aims to evaluate the reliability and validity of the Brazilian version of the RESVECH 2.0 instrument in the context of difficult-to-heal wounds. Methods: A methodological study was carried out. Initially, participants were interviewed in order to establish a profile; then evaluations of difficult-to-heal wounds of any etiology (n = 179) were performed with RESVECH 2.0 and Pressure Ulcer Scale for Healing 3.0 (PUSH 3.0) instruments. Results: The psychometric properties evaluated were convergent construct validity, interobserver reliability and internal consistency. Internal consistency reliability showed the values of 0.561 and 0.535. Interobserver reliability showed a Kappa value ranging from 0.14 to 0.76 and an intraclass correlation coefficient (ICC) of 0.87. For convergent construct validity, Spearman’s correlation coefficient was applied to RESVECH 2.0 and PUSH 3.0 scores (n = 150); the coefficient obtained was 0.717. Conclusion: It is concluded that the instrument showed evidence of reliability and validity.